The effect of iron and iron chelators on the growth of an in vitro plasmodium falciparum culture. - Jairam, Karuna Thaker (My University, 1991)
The influence of iron on the outcome of various infections have been extensively reviewed. Clinical observations suggests that iron deficiency may be protective against malaria. Various researchers have shown that certain iron chelators blocked the proliferation of plasmodium falciparum in vitro and in vivo. (Abbreviation abstract)
A DISSERTATION SUBMITTED TO THE FACULTY OF MEDICINE, UNIVERSITY OF THE WITWATERSRAND, JOHANNESBURG, FR THE DEGREE OF MASTER OF SCIENCE IN MEDICINE.
Keywords: Plasmodium falciparum.; Malaria drug therapy.; Malaria prevention & control.; Iron.; Iron Chelates.